Proceedings of the 3rd Workshop on Software Engineering in Health Care 2011
DOI: 10.1145/1987993.1987996
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of apparent causes and outcomes of reported failures with patient management software

Abstract: Patient management software (PMS) plays an increasingly critical role in the operation of modern health care systems. While more PMS systems are coming online, many practitioners have raised concerns regarding the quality of such systems, in particular with respect to safety. Recently, the software engineering research community has stepped up efforts investigating the specific challenges in health care in order to translate best engineering practices to this domain. While incidental reports about failures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In 2010, The Huffington Post Investigative Fund with help of the FDA, identified and extracted 237 reports that were submitted over a period of roughly two years (Jan. 08 to Feb. 15, 10). In earlier work, we analyzed these reports with respect to the identification of apparent causes for the reported errors and the device type associated with the malfunctions [32]. The description of the majority of reported incidents either indicate a potential for injuries or the actual occurrences of injuries or death.…”
Section: Emr Errors Reported In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, The Huffington Post Investigative Fund with help of the FDA, identified and extracted 237 reports that were submitted over a period of roughly two years (Jan. 08 to Feb. 15, 10). In earlier work, we analyzed these reports with respect to the identification of apparent causes for the reported errors and the device type associated with the malfunctions [32]. The description of the majority of reported incidents either indicate a potential for injuries or the actual occurrences of injuries or death.…”
Section: Emr Errors Reported In Practicementioning
confidence: 99%
“…While researchers have initially published predominantly about (potential) safety benefits of EMRs, observed in experiments with prototypes in carefully controlled environments, voices have become far more critical when it comes to experiences with commercial EMR products in day to day health care practices [4,19,7]. Caregivers and practitioners have alerted the industry and governments about unforeseen and potentially dangerous 'sideeffects' of EMRs [32]. There is mounting pressure on regulators to put in place mechanisms that assure the safety of health systems using EMRs [30,33,12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, customers are becoming concerned about the quality of software delivered to them 1,2 . Nevertheless, there still exist complains about customers' dissatisfactions 3,4 . The study by Standish Group indicated that the success rate of software projects has decreased, from 35% in year 2006 to 32% in year 2009.…”
Section: Introductionmentioning
confidence: 99%